Ultracompact Si-GST Hybrid Waveguides for Nonvolatile Light Wave Manipulation - Hanyu Zhang; Linjie Zhou; B. M. A. Rahman; Xing Wu; Liangjun Lu; Youhua Xu; Jian Xu; Junchao Song; Zhigao Hu; Liping Xu; Jianping Chen (IEEE Photonics Journal)
Phase change materials combined with silicon photonics are emerging as a promising platform to realize miniature photonic devices. We study the basic optical properties of a subwavelength-dimension silicon ridge waveguide with a 20-nm-thick Ge2Sb2Te5 (GST) top-clad layer. Numerical simulations show that the effective index of the Si-GST hybrid waveguide varies significantly when the GST changes from the amorphous to the crystalline states. This change can be utilized to make micron-size photonic devices. To experimentally verify the effectiveness of the Si-GST hybrid waveguide on light wave manipulation, we fabricated a series of unbalanced Mach–Zehnder interferometers with one arm connected with a section of Si-GST hybrid waveguide in different lengths. The transmission spectra are measured and the complex effective indices are extracted for GST at crystalline, amorphous, and intermediate phases. The experimental results overall agree well with the simulation ones. The nonvolatile property of GST makes it attractive to reduce the static power consumption. This research represents a significant step toward the realization of ultracompact Si-GST hybrid devices that will play a key role in high-density photonic integrated circuits, opening the door to many potential applications, including optical switch, memory, and logic operation.